The Effect of Learning Strategy and Critical Thinking Ability on English Essay Writing Skills - Lisdwiana Kurniati; Wanawir Abdul Muin (International Journal of Educational Research Excellence (IJERE), 2022)
The Informatics Engineering Study Program at Mitra Karya University Bekasi has two English courses given in semesters 1 and 3. In semester I, students study English which is directed at understanding grammatical and vocabulary in the field of Informatics Engineering. Students must be able to write a minimum of three paragraphs about their field. Learning to write essays is also aimed at mastering thesis abstract writing. Writing is one aspect of productive language skills. For this reason, the principle of teaching writing is how to make students have sufficient competence in an effort to produce good writing skills in students. However, the process of learning to write English essays is not as easy as expected so far. Students still experience many difficulties in writing essays, this causes the quality of the content of their English essays to be not optimal. Even though it is known that students should be able to react critically when reading an essay text that is presented either on a website, newspaper, magazine, or book. This study uses an experimental method and a quantitative approach, while the data collection technique is carried out by means of observation, tests and documentation, so the results of this study explain that from the results of the description of descriptive statistical data it is known that the average value of students who learn to write English essays using metacognitive strategies had an average score of 81.5 higher than students who studied with cognitive strategies.